2011
DOI: 10.1007/s00436-011-2464-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional differences between hypobiotic and non-hypobiotic preadult larvae of the bovine lungworm Dictyocaulus viviparus

Abstract: The survival of the bovine lungworm Dictyocaulus viviparus, one of the most important parasites in cattle, inside the host is ensured by arrested development during adverse environmental conditions, commonly referred to as hypobiosis. In the present study, a subtractive hybridization approach was used to compare the transcription profiles of hypobiotic and non-hypobiotic larvae (L5hyp and L5, respectively). Thereby, 75 L5hyp-enriched and 58 L5-enriched representative ESTs (rESTs) were identified. Subsequent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…We specifically explored transcription in hypobiotic L5 (L5hyp) in an attempt to infer the molecular mechanism(s) responsible for maintenance of the parasite’s developmental arrest within the host animal, a process critical to the year-to-year survival of D. viviparus in temperate regions. Although L5hyp have undergone the final molt, they are smaller than active L5 and have an underdeveloped genital primordium 16 . Interestingly, the transcriptome profile of L5hyp was more similar to L4 than active L5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We specifically explored transcription in hypobiotic L5 (L5hyp) in an attempt to infer the molecular mechanism(s) responsible for maintenance of the parasite’s developmental arrest within the host animal, a process critical to the year-to-year survival of D. viviparus in temperate regions. Although L5hyp have undergone the final molt, they are smaller than active L5 and have an underdeveloped genital primordium 16 . Interestingly, the transcriptome profile of L5hyp was more similar to L4 than active L5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 217 genes were significantly overexpressed in L5hyp compared with L4 ( Supplementary Table S8 ), and these were enriched for GO terms associated with proteolysis, response to heat, and lipid transport ( Supplementary Table S7 ). A previous study suggested that an upregulation of transcription factors might aid in the initiation and maintenance of the hypobiotic state 16 . We identified 11 TFs among the 417 genes, which are differentially transcribed between L4 and L5hyp, although they are not significantly over-represented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations